CONSUMER’S PERCEPTION TOWARDS THE PURCHASE OF ECO-FRIENDLY ORGANIC DAIRY MILK PRODUCTS IN TIRUNELVELI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study is to understand what influences consumers' decisions to purchase eco-friendly organic dairy milk products. Since the beginning of agriculture, interest in eco-friendly organic farming has increased. Environmental protection is given first priority in eco-friendly organic farming, raising the environmental standard. Customers are prepared to spend more to protect their health from illnesses. Customers are interested in purchasing eco-friendly organic food because it doesn't have any pesticides or chemical residues. Due to its alleged advantages over conventional food, many are now willing to eat eco-friendly organic food. The current study, which focuses on how consumers perceive eco-friendly organic dairy milk products, was conducted with a sample size of 150 consumers of eco-friendly organic dairy milk products in the Tirunelveli District. A standard questionnaire was used to randomly solicit customers, and the basic data was then analyzed using software. This study aims to investigate the level of satisfaction and reasons to purchase the eco-friendly organic dairy milk products.